Controlled Synthesis and Photocatalytic Activity of TiO2 Nanoparticles by a Novel Gel-Network Precipitation Method - Wang, Yingling; Xie, Youhai; Yuan, Jianmei; Liu, Guoguang (Asian Journal of Chemistry, 2012)
Using gelatin as a based template, monodispersed spherical TiO2 nanoparticles were successfully synthesized by a novel gel-network precipitation(GNP) method. The well-crystallized anatase TiO2 have narrow size distribution of 20 nm. The aim of our work was to investigate the influence of reaction conditions on the formation process, structure and photocatalytic activity of the samples. TG-DTA, XRD, TEM, FT-IR, UV-VIS DRS and HPLC were used to characterize the samples. The results showed that the particle sizes were related to the network structure of gelatin, not only could the crystalline phases and sizes of nanoparticles be controlled, but the aggregation and agglomeration could be prevented by gel-network. The products have smaller particle size and better homogeneity. To examine the photocatalytic activity of the samples, the photocatalyic degradation rate of rhodamine B (RB) was investigated in the suspension of TiO2 nanoparticles. It was found that well-crystallized anatase TiO2 (y = 8 %) calcined at 650 ºC for 2 h nearly induced complete degradation of rhodamine B. Relationship between degradation rate of rhodamine B and grain sizes of TiO2 nanoparticles under different gelatin concentration and calcination temperature were given. The enhancing of the photocatalytic activity was attributed to the increase of phase transformation temperature and uniformity of the particle sizes.